A Hematological Triad: Dissecting Synergistic Oxidative and Immune Hemolysis in Dapsone-Treated G6PD Deficiency - Devina Ravelia Tiffany Subroto; I Putu Bayu Triguna (Open Access Indonesian Journal of Medical Reviews, 2025)
Dapsone, a key component of leprosy multidrug therapy (MDT), is a well-known precipitant of oxidative hemolytic anemia in individuals with Glucose-6-Phosphate Dehydrogenase (G6PD) deficiency. Conversely, Dapsone-induced immune hemolytic anemia (DIIHA) is exceedingly rare. The concurrent presentation of both severe oxidative hemolysis and a positive Direct Antiglobulin Test (DAT) in a patient also receiving Rifampicin creates a profound diagnostic and mechanistic challenge. We present the case of a 42-year-old female with multibacillary leprosy who developed life-threatening, multifactorial hemolytic anemia (Hemoglobin 5.3 g/dL) three months after initiating MDT (Dapsone, Rifampicin, Clofazimine). A comprehensive diagnostic workup was performed, including detailed hematopathology and quantitative G6PD assay. The immunohematological evaluation was positive (DAT and IAT), but critical sub-testing, including monospecific DATs, was unavailable. The workup confirmed severe oxidative hemolysis (Heinz bodies, degmacytes) in the setting of G6PD deficiency (6.0 U/g Hb measured during 12.5% reticulocytosis). Concurrently, the polyspecific DAT and IAT were strongly positive with a pan-reactive antibody, confirming a simultaneous immune-mediated process. Due to polypharmacy (Dapsone, Rifampicin) and incomplete immunohematological data, the precise trigger for the DIIHA component—whether a rare Dapsone-induced autoantibody, a Rifampicin-induced immune-complex, or an oxidative-trigger mechanism—could not be definitively isolated. In conclusion, this case unmasks a complex, synergistic pathophysiology of concurrent oxidative and immune hemolysis. The inability to attribute the autoimmune component definitively to either Dapsone or Rifampicin highlights a critical diagnostic gap. This report underscores the necessity of a complete immunohematological workup (including monospecific DATs) in such cases and demonstrates that management must be multifaceted—addressing both the oxidative insult (drug cessation) and the severe immune-mediated destruction (immunosuppression), even in the face of etiological uncertainty.